THE CULTURAL RELATIONSHIP BETWEEN ENGLISH’S AND INDIANS AS REFLECTED IN “A PASSAGE TO INDIA” BY E.M FOSTER; A POST COLONIAL ANALYSIS - M.Hum, Robby Satria (Menara Ilmu, 2018)
This research discusses the application of Post Colonial theory proposed by EdwardSaid which proposed that literary work in post colonial period has the reflection of thesituation of colonization at the certain time. In this research the writer analyses the novel APassage to India written by E.M. Foster published in 1816. Here, the writer analyses thecultural relationship between English and India in colonial period.This research is qualitativeresearch by using descriptive method. Data is gained by library research method and othersources taken from web. In this research, the data is analysed based on its relationship withthe purpose of the research both instrinsic and extrinsic element in literary work.Afterapplying post colonial theory of Orientalism by Edward Said to” The Passage to India” thewriter found in the beginning, there was a good relationship between english’s and Indians,but in the end, the culture clash occurs which finally create the incident between two countries.